2017
DOI: 10.1055/s-0043-107245
|View full text |Cite
|
Sign up to set email alerts
|

3D Volumetric Measurements of GH Secreting Adenomas Correlate with Baseline Pituitary Function, Initial Surgery Success Rate, and Disease Control

Abstract: There is scarce data on the clinical utility of volume measurement for growth hormone (GH)-secreting pituitary adenomas. The current study objective was to assess the association between pituitary adenoma volumes and baseline endocrine evaluation, initial surgical success rate, and disease control among patients with acromegaly. A retrospective cohort study was conducted at a clinical research center including patients with acromegaly due to GH-secreting pituitary adenomas. Baseline hormonal evaluation and ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
4
2
Order By: Relevance
“…In Tirosh et al. study ( 25 ) an association between tumor volume and hypogonadism was determined, more pronounced in males, which was not obtained in our study. In that study also an association between size of tumor > 10 mm before the operation and the need for re-operation was observed.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In Tirosh et al. study ( 25 ) an association between tumor volume and hypogonadism was determined, more pronounced in males, which was not obtained in our study. In that study also an association between size of tumor > 10 mm before the operation and the need for re-operation was observed.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of diabetes in acromegaly patients is 12% to 53% ( 17 , 19 , 30 , 33 , 34 ). We observed diabetes in 33% of the cases and prediabetes in 34%, which is much higher than in the general Polish population (6.97%) ( 25 ). In Warncke’s study, it has been reported that in acromegaly diabetes affects younger patients (50.1 years) than in the general population (59 years) ( 35 ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This tracing included any bulges of the contour caused by nodules or masses in the adrenal periphery. The adrenal volume was calculated from the sum of each axial slice area …”
Section: Methodsmentioning
confidence: 99%
“…This tracing included any bulges of the contour caused by nodules or masses in the adrenal periphery. The adrenal volume was calculated from the sum of each axial slice area 19,20. Adrenal morphology was categorized as normal, atrophy, hyperplasia with or without nodules (<5mm), adrenocortical adenomas (≥5mm), myelolipoma or other.…”
mentioning
confidence: 99%